Konsistensi Teori Belajar dan Pembelajaran dalam Pendidikan - Nailatur Rohmah; Maimon Sumo; Sofweturrohmah; Ratno Budiyanto (PT. Penerbit Tiga Mutiara, 2024)
Education is the backbone and main tool for a country’s development, because it emphasizes the quality of human resources (HR). Education aims to brighten the nation’s future with an intelligent and characterful generation. Learning, as an interaction between teachers, students, and learning resources, is a systematic process involving interrelated components to achieve optimal results. This literature review aims to provide a comprehensive understanding of learning theory and learning in educational practice. In this research, the researcher used a literature review method which aims to identify, find and analyze documents related to the research problem. The results of the research show that this consistency has a crucial role in creating a predictive learning environment, facilitating the continuity of curriculum and strategy development. teaching, facilitates the transfer of learning, and forms a strong foundation for an effective and sustainable learning experience for students. Consistency in applying learning and learning theories, such as behaviorism, cognitivism, constructivism, and humanism, helps educators in designing structured and directed learning. This allows students to develop a deep understanding of the subject matter and skills that are important for learning. In conclusion, the consistency of learning and learning theories in education is an important factor for achieving educational goals. By consistently applying learning theories, an intelligent and characterful generation can be created that is ready to build a brighter future for the nation.